Development of Laboratory Module of Isolation Trimyristin from Nutmeg (Garcinia mangostana) to Support Meaningful Learning in Natural Product Chemistry Course - Hakim, Aliefman; Jamaluddin, Jamaluddin; Jufri, Abdul Wahab; Loka, I Nyoman; Sukib, Sukib; Mahmudah, Saripatul (Jurnal Penelitian dan Pembelajaran IPA, 2019)
This research aimed to develop laboratory module of isolation trimyristin from nutmeg (Garcinia mangostana) to support natural product chemistry course. The research design used 4D model (Define, Design, Develop, and Disseminate). The population in this study covers all students of Chemistry Education Program, University of Mataram who took natural product course. Meanwhile there were four students who became the sample in this study. The four students were taken randomly and became respondents for a limited trial. The results showed that the validity of three validators obtained by using Aiken index was V = 0.7 indicated that the natural chemistry laboratory module about trimyristin isolation from nutmeg was valid and feasible to use. Practicality can be seen from the responses of students and lecturers who showed a positive response with the average of all module component practicability of 83%. Based on the data, it can be concluded that the natural chemistry labortory module of isolation trimyristin from nutmeg was feasible and practical, so it can be used in the learning process.